(untitled) (World Bulletin of Public Health, 2022)
Objectives: 1-To assess Effect of Tocophobia on Pregnancy Outcome among Pregnant Women 2-To find the relationship between Tocophobia and demographic data ( age, educational level and husband educational level). Methodology: A descriptive and analytic study design, cross sectional design about the Effect of Tocophobia on Pregnancy Outcome among Pregnant Women. A purposive sampling (nonprobability) consists of (100) pregnant women in 3rd trimester who had signs and symptoms of Tocophobia at Maternity and Pediatric Hospital in AL-Samawa City. (W-DEQ) scale used to measure the fear of childbirth, data was collected from 1 April to 30 June 2022. Determined validity through panel of experts of the questionnaire and Reliability through pilot study (20) of pregnant women, descriptive and inferential statistic procedures and the data were collected through interview technique. Results: the results show that average mean score and SD of study sample is (22±4) years, in which more of them are young women in age group (21 - 30) years (70%). shows presents the variables related to reproductive history of study sample ; the finding shows that the average (M ± SD) of Age at marriage is (20±3) years and (53%) of pregnant women are married at age. shows assessment is based on mean of score for item responses; the higher mean of score= extremely and the lower mean of score= not significant (reversed based on question direction). shows indicates that there is no significant relationship between signs and symptoms of Tocophobia among study sample with demographic characteristics ( age , educational level and husband educational level) at p-value= 0.05. Recommendations: Nurse /midwife need to deal and counseling with childbirth fear by providing appropriate information about pregnancy and labour during pregnancy through lecture, films, and preparation classes.